Development of an Aging-Related Gene Signature for Predicting Prognosis, Immunotherapy, and Chemotherapy Benefits in Rectal Cancer - Wang, Yangyang; Liu, Yan; Zhu, Chunchao; Zhang, Xinyu; Li, Guodong (Frontiers in Molecular Biosciences, 2022)
Objective: Aging is the major risk factor for human cancers, including rectal cancer. Targeting the aging process provides broad-spectrum protection against cancers. Here, we investigated the clinical implications of aging-related genes in rectal cancer. Methods: Dysregulated aging-related genes were screened in rectal cancer from TCGA project. A LASSO prognostic model was conducted and the predictive performance was evaluated and externally verified in the GEO dataset. Associations of the model with tumor-infiltrating immune cells, immune and stromal score, HLA and immune checkpoints and response to chemotherapeutic agents were analyzed across rectal cancer. Biological processes underlying the model were investigated through GSVA and GSEA methods. Doxorubicin (DOX)-induced or replicative senescent stromal cells were constructed and AGTR1 was silenced in HUVECs. After co-culture with conditioned medium of HUVECs, rectal cancer cell growth and invasion were investigated. Results: An aging-related model was established, consisting of KL, BRCA1, CLU and AGTR1, which can stratify high- and low-risk patients in terms of overall survival, disease-free survival and progression-free interval. ROC and cox regression analyses confirmed that the model was a robust and independent predictor. Furthermore, it was in relation to tumor immunity and stromal activation as well as predicted the responses to gemcitabine and sunitinib. AGTR1 knockdown ameliorated stromal cell senescence and suppressed senescent stromal cell-triggered rectal cancer progression. Conclusion: Our findings suggested that aging-related gene signature was in relation to tumor immunity and stromal activation in rectal cancer, which might predict survival outcomes, immuno- and chemotherapy benefits.